Produção do livro escolar em línguas africanas: o caso da ADPP-Moçambique - Magona, Vasco (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
This study is part of a lager ethnography research developed in 5 rural primary schools of Matutuine and Manhiça Districts in Maputo province. The research involved 35 teachers, 5 school managers, 6 focus groups with parents and other community members and 2 representatives of Development Aid from People to People (ADPPMozambique). In this article I discuss, in reflexive and critical way, the extent to which these models of textbook organization, procedures and practices adopted by ADPP-Mozambique are or not adequate for the production of textbooks in multilingual and multicultural contexts, as it is the case of Mozambique, based on the concepts of decoloniality (Mignolo, 2009, 2011, 2013) and linguistic citizenship (Stroud, 2001, 2018). The results of the present study point out a breaking up with the ‘traditional’ procedures used by Ministério da Educação e Desenvolvimento Humano (MINEDH) in the production of textbooks in African languages. Despite this rupture, the results of the study show that there is a lack of community participation in the production of the textbook. Given this asymmetric framework, community voices are not addressed.